Kajian Parasitoid: Eriborus Argenteopilosus Cameron (Hymenoptera : Ichneumonidae) pada Spodoptera. Litura fabricius (lepidoptera : Noctuidae) - Nelly, Novri; Yaherwandi, Yaherwandi; Gani, S.; Apriati, Apriati (Lembaga Penelitian Universitas Negeri Padang, 2008)
Study of parasitoid Eriborus argenteopilosus Cameron (Hymenoptera : Ichneumonidae) on S. litura Fabricius (Lepidoptera: Noctuidae) was conducted in laboratorium Entomology Departement Plant pest and desease Faculty of agriculture, Andalas University in January to March 2006. The study was used biological assay methode to known parasititation and potential fecundity of parental parasitoid. The result showed that fluctuation parasititation (63 - 17,99 %) and superparasitisme (36,67 - 3,33%) E. argenteopilosus on S. litura Potential fecundity of E. argenteopilosus 182,3±72 and potential release 73,7±49 eggs. The survival of parental adult E. argenteopilosus only 6 days in laboratorium. Key words : E. argenteopilosus, Parasititation, S. litura